Observing the nonvectorial yet cotranslational folding of a multidomain protein, LDL receptor, in the ER of mammalian cells - Kadokura, Hiroshi (Proc Natl Acad Sci U S A, 2020)
Proteins have evolved by incorporating several structural units within a single polypeptide. As a result, multidomain proteins constitute a large fraction of all proteomes. Their domains often fold to their native structures individually and vectorially as each domain emerges from the ribosome or the protein translocation channel, leading to the decreased risk of interdomain misfolding. However, some multidomain proteins fold in the endoplasmic reticulum (ER) nonvectorially via intermediates with nonnative disulfide bonds, which were believed to be shuffled to native ones slowly after synthesis. Yet, the mechanism by which they fold nonvectorially remains unclear. Using two-dimensional (2D) gel electrophoresis and a conformation-specific antibody that recognizes a correctly folded domain, we show here that shuffling of nonnative disulfide bonds to native ones in the most N-terminal region of LDL receptor (LDLR) started at a specific timing during synthesis. Deletion analysis identified a region on LDLR that assisted with disulfide shuffling in the upstream domain, thereby promoting its cotranslational folding. Thus, a plasma membrane-bound multidomain protein has evolved a sequence that promotes the nonvectorial folding of its upstream domains. These findings demonstrate that nonvectorial folding of a multidomain protein in the ER of mammalian cells is more coordinated and elaborated than previously thought. Thus, our findings alter our current view of how a multidomain protein folds nonvectorially in the ER of living cells.